2018
DOI: 10.1007/s00268-018-4496-y
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Outcomes After Pancreatectomy for Pancreatic Ductal Adenocarcinoma in Elderly Patients: Special Reference to Postoperative Adjuvant Chemotherapy

Abstract: The benefit of pancreatectomy for PDAC was the same between young and elderly patients. Completion of planned AC was important, and lowered-dose AC using S1 for elderly patients might be safe and therapeutically useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 51 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…Previous studies on OS in elderly reported no statistically significant difference between older and younger patients (median 9–26 vs. 12–24 months), and age was not independently associated with OS in multivariable analysis. 8 , 15 , 19 , 24 , 31 Moreover, DFS was comparable between both age groups (median 7–13 vs. 15 months). 19 , 53 Our results show significant differences in median OS and DFS for patients aged ≥ 75 years when compared with patients aged <75 years, i.e.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Previous studies on OS in elderly reported no statistically significant difference between older and younger patients (median 9–26 vs. 12–24 months), and age was not independently associated with OS in multivariable analysis. 8 , 15 , 19 , 24 , 31 Moreover, DFS was comparable between both age groups (median 7–13 vs. 15 months). 19 , 53 Our results show significant differences in median OS and DFS for patients aged ≥ 75 years when compared with patients aged <75 years, i.e.…”
Section: Discussionmentioning
confidence: 84%
“… 8 , 15 , 19 , 24 , 31 Moreover, DFS was comparable between both age groups (median 7–13 vs. 15 months). 19 , 53 Our results show significant differences in median OS and DFS for patients aged ≥ 75 years when compared with patients aged <75 years, i.e. 15 versus 21 months ( p < 0.001) and 12 versus 16 months ( p < 0.001).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations